THE DEVELOPMENT OF ISLAMIC STUDIES IN THE WESTERN WORLD - Julhadi, Julhadi; Dina, Hidayatul; Candra, Aldi Gustika; Hirawan, Robi; Astirani, Fuspita (at-Tahsin, 2023)
The golden ink of Islamic civilization which has long dominated the world certainly makes Islam a phenomenon worthy of study throughout the world, especially by people outside of Islam. Westerners in particular. They research, conduct studies, and make Islam an object of study in their world of education. Moreover, it is supported by the methodological advantages they have. .With this background, the author wants to examine in depth related to Islamic studies in the Western world, especially in the academic world. Hopefully it can provide overall benefits. From this background, several problems can be formulated to be examined in this paper, including: What is the essence of Islamic studies? How is the history of Islam?studies in the Western world? From the presentation of Islamic studies in the West in the academic world that has been mentioned in the previous chapter, it can be concluded that: (1) Islamic studies are an attempt to know and understand and discuss in depth the ins and outs of matters relating to Islam from various aspects. By holding Islamic Studies, it is hoped that it will be able to increase the understanding and appreciation of Muslims wherever they are; (2) Islamic studies when viewed from a research perspective, can be grouped into two, insiders and outsiders. Islamic studies by Muslims themselves in classical times tended to use a continuous pattern from generation to generation. The pattern has shifted in the present, which tends to become a pattern critical. While the perspective of outsiders, Islamic studies are critical in various aspects because they are based on an attitude of self-defense against the beliefs that they believe in so far; (3) The history of Islamic studies in the Western academic world has existed for a long time. That long history is broken down into three according to the aims and content of Islamic studies. The three stages include: the theological stage, the political stage and the scientific stage; (4) It can be seen the condition of Islamic studies in the Western academic world from the proliferation of centers for Islamic studies in various countries, both in America and Europe. Many Islamic study centers have sprung up in the United States, Chicago, Holland, Germany, London and so on.